What drives housing prices down? Evidence from an international panel - Konstantin Arkadievich Kholodilin; Jan-Oliver Menz; Boriss Siliverstovs (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
In this study, we suggest an explanation for the alarmingly low growth rates of real housing prices in Canada and Germany in comparison to other OECD countries over 1975-2005. We show that the long-run development of housing markets is determined by real disposable per capita income, real long-term interest rate, population growth, and urbanization. The differential development of real housing prices in Canada and Germany is attributed to the specific values of the fundamentals in these two countries. Canada and Germany are characterized by relatively low average growth rates of real disposable income and relatively high interest rates resulting in suppressed housing prices over long period of time. Institutional structure accentuates these tendencies. Given the importance of housing wealth for the private consumption, our paper aims at drawing attention of the policymakers to the necessity of preventing not only the overheating but also overcooling of the housing market that entails lower economic growth rate.
Keywords: E30; C23; C51; 330; house prices; dynamic panel data; cointegration; Immobilienpreis; Preisniveau; Realzins; Kanada; Deutschland; OECD-Staaten